Property predictions demonstrate that structural diversity can improve the performance of polyoxymethylene ethers as potential bio-based diesel fuels. (1st July 2021) - Bartholet, Danielle L.; Arellano-Treviño, Martha A.; Chan, Fan Liang; Lucas, Stephen; Zhu, Junqing; St. John, Peter C.; Alleman, Teresa L.; McEnally, Charles S.; Pfefferle, Lisa D.; Ruddy, Daniel A.; Windom, Bret; Foust, Thomas D.; et al.
Highlights: Polyoxymethylene ethers are novel molecules that may reduce diesel soot production. Branched POME variants and end groups are evaluated for the first time. Properties of 67 POMEs structures were evaluated using structure–activity models. Molecules were screened for reduced sooting tendency and good fuel performance. Nine POMEs were identified as promising oxygenated diesel fuel blendstocks. Abstract: High emissions of particulate matter from diesel engines presents a serious risk to human health and the environment. The addition of oxygenated molecules to diesel fuels has been shown to reduce soot formation during combustion. Polyoxymethylene ethers (POMEs) are a novel class of oxygenated molecules that can be produced from biomass and that have the potential to be used as soot-reducing diesel fuel blendstocks. However, only a few variations of these molecules have been studied thus far, and those that have been characterized present significant disadvantages that could compromise current liquid fuel systems and diesel engines. Using a variety of structure–activity models, we evaluated 67 POMEs to predict the effects of structural variations on important fuel properties. Prediction accuracy was assessed by comparing predictions with measurements for a subset of structures. Nine POME molecules were identified as having potential to reduce soot formation by over 75% compared to conventional diesel fuels while being compatible with current liquid fuel infrastructure, maintaining optimal engine performance, and presenting a minimal risk to the environment. None of these nine POMEs has been previously identified as a potential diesel blendstock. This is the first evaluation of POMEs as a class of molecules and the results guide research on the synthesis, properties, and engine performance of POMEs.